2002
DOI: 10.1017/s1355838202023014
|View full text |Cite
|
Sign up to set email alerts
|

The dispersal of five group II introns among natural populations of Escherichia coli

Abstract: Group II introns are self-splicing RNAs that also act as retroelements in bacteria, mitochondria, and chloroplasts. Group II introns were identified in Escherichia coli in 1994, but have not been characterized since, and, instead, other bacterial group II introns have been studied for splicing and mobility properties. Despite their apparent intractability, at least five distinct group II introns exist naturally in E. coli strains. To illuminate their function and learn how the introns have dispersed in their n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 24 publications
3
31
0
Order By: Relevance
“…EcI5 is a CL/IIB1 intron, whose IEP contains an En domain ( Fig. 1; Burland et al 1998;Dai and Zimmerly 2002b). We found that EcI5 is highly active in retrohoming.…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations
“…EcI5 is a CL/IIB1 intron, whose IEP contains an En domain ( Fig. 1; Burland et al 1998;Dai and Zimmerly 2002b). We found that EcI5 is highly active in retrohoming.…”
Section: Introductionmentioning
confidence: 67%
“…The intron is inserted within a noncoding region of the plasmid, but in the same orientation as most other plasmid genes. Southern hybridizations and PCR analysis showed that EcI5 is also inserted at the same site in DNAs isolated from 19 of 72 ECOR strains, although always in fragmented form (Dai and Zimmerly 2002b). By using the computer algorithm developed here for identifying EcI5 target sites, we found no efficient target sites for the wildtype intron (log-odds score > 8.2 and Watson-Crick or wobble base pairs at all EBS/IBS positions) in sequenced E. coli O157 genomes (EC4115, EDL933, and Sakai), and only one such target site in the nonessential gene cusS in the genome of E. coli K12 MG1655, which does not carry the plasmid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, the distribution of group II introns across bacterial species and strains is sporadic (44,54,57,58). For example, related strains of Escherichia coli can harbor from one to 15 copies of group II introns (59), and some genomes contain over 20 identical copies of an intron (60).…”
Section: Group II Introns: the Prototypical Bacterial Retroelementmentioning
confidence: 99%